Harrison's neurology in clinical medicine 2026-02-15T19:24:26+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Harrison, Tinsley Randolph, 1900-1978; Hauser, Stephen L; Josephson, Scott Andrew (McGraw-Hill Medical, 2010)

(untitled)
"This book provides an easy-to-use format and full coverage of the most authoritative information available anywhere of clinically important topics in neurology and psychiatry, while retaining the focus on pathophysiology and therapy that has always been characteristic of Harrison's Principles of Internal Medicine"--Provided by publisher